Effectiveness of The Project Task Based on Potential of Student’s Region on Student Engagement - ., Syahril (Opción, 1970)
This study aimed to investigate ‘what does the project task of region potential can make students possible to act more active with the high involvement of learning?’ This study used proactive action research that focused to the new way to improve students’ engagement. The assessment of students’ engagement was carried out using questionnaire and strengthened by qualitative data, were follows: lecturers’ observation result and students’ interview. The result of this study shown that the implementation of project based on potential of student’s region was effective to make students engage with the learning process. The factor that make high students’ engagement was the project task that has been done, it was very useful for their region.